An investigation study on leisure reading habits of pre-service teachers in Universiti Teknologi MARA Melaka / Azim Mohammad Allaudin - Mohammad Allaudin, Azim (2011)
This study investigated the reading habits of the pre-service teachers in UiTM Melaka. It was conducted for the purpose to answer three research questions which are first, do pre-service teachers in UiTM Melaka read for leisure. Second, what types and genre of materials do the pre-service teachers in UiTM Melaka read in their leisure time and finally what are the reading habits of the pre-service teachers in UiTM Melaka. The research design employed for this study is non-experimental descriptive survey research design. The instrument used for this study is a structured questionnaire developed by the researcher and a pilot study was conducted to determine the reliability value of the questionnaire based on Cronbach’s Alpha method. The subjects involved in this study were 47 pre-service teachers in UiTM Melaka. The data gathered was then analyzed by using SPSS version 19 software. The findings of this study show that the pre-service teachers of UiTM Melaka indicated that they do read for leisure however it was found that the majority of them falls under the category if rare readers. It was also found that these future teachers only read light materials such as magazines and newspapers and only a small number of participants read books in their free time. This study also provides pedagogical implications for the higher learning institutions, teachers and students, limitations of the study and recommendations for future research.